Development of novel monoclonal antibodies for blocking NF-κB activation induced by CD2v protein in African swine fever virus - Fan, Rongrong; Wei, Zeliang; Zhang, Mengmeng; Jia, Shanshan; Jiang, Zhiyang; Wang, Yao; Cai, Junyu; Chen, Guojiang; Xiao, He; Wei, Yinxiang; Shi, Yanchun; Feng, Jiannan; et al. (Frontiers in Immunology, 2024)
The highly contagious African swine fever virus (ASFV) poses a significant threat to the pig industry. Monoclonal antibodies (mAbs) targeting ASFV have shown promise for diagnosing and combating African swine fever (ASF). CD2v, a key outer envelope glycoprotein of ASFV encoded by the EP402R gene, plays a critical role in the hemadsorption phenomenon during ASFV infection and has been recognized as an essential immunoprotective protein. In this study, we used eukaryotic cells to express recombinant CD2v and generated murine mAbs against it using rigorous screening and cloning of hybridomas. We characterized the mAbs using various techniques including indirect enzyme-linked immunosorbent assay (ELISA), western blotting, immunofluorescence assay (IFA), and bio-layer interferometry (BLI). We successfully identified an optimal antibody pair to develop a highly sensitive sandwich ELISA after conducting a competitive ELISA. Furthermore, we investigated the antigenic structures recognized by the mAbs using epitope mapping involving truncation mutants and epitope peptide mapping. Among the epitopes of the mAbs, two targeted linear epitopes were highly conserved in ASFV genotype II strains, particularly in Chinese endemic strains. Another mAb recognized a unique glycosylated epitope. Importantly, our findings revealed that three mAbs, namely 2B25, 3G25, and 8G1, effectively blocked CD2v-induced NF-κB activation. Overall, this study provides valuable insights into the antigenic structure of ASFV CD2v. The mAbs obtained in this study have great potential for use in the development of ASF diagnostic strategies and vaccine designs.